Enhancing Third-grade Students’ Learning Outcomes in Mathematics through Fraction Puzzle Activities - Fratiwi, Nuzulira Janeusse; Muhtarudin, Muhtarudin (Magister Manajemen Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2024)
This study seeks to improve the learning results of third-grade elementary school pupils by incorporating fraction puzzles into mathematics instruction. The research used the Classroom Action Research (CAR) approach, which was carried out in four stages: preparation, implementation, observation, and reflection. The study included 20 third-grade pupils as subjects, with 10 boys and 10 girls. The instrument employed was a multiple-choice test. Data analysis demonstrated an improvement in students' learning outcomes, with an average score going from 69.6 in the initial phase to 76 in the first cycle and then to 84.2 in the second cycle. Based on these data, it is concluded that the usage of fraction puzzles in mathematics education can improve students' learning outcomes. Future study should focus on using image-based media as a learning aid to increase student attention and improve mathematical learning results.